2016
DOI: 10.4103/0973-1482.200600
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of perioperative outcomes between laparoscopic and open surgery for mid-low rectal cancer with total mesorectal excision following neoadjuvant chemoradiotherapy

Abstract: We concluded that laparoscopic TME following nCRT is feasible and safe for patients with mid-low rectal cancer. Furthermore, tumor distance to anal verge and age are two important determinants of both operative times and postoperative morbidity, regardless of surgical option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…LTME has risen to become the gold standard for rectal cancer suitable for surgical resection[ 7 ]. Many trials including the COLOR II trial established that it gave similar oncological outcomes compared to an open approach[ 8 , 9 ] and further studies showed it resulted in shorter length of stay, less pain and quicker resumption of normal diet[ 10 , 11 ]. The main reason behind these proven advantages of the laparoscopic TME is the reduced surgical trauma and tissue handling compared to open TME.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LTME has risen to become the gold standard for rectal cancer suitable for surgical resection[ 7 ]. Many trials including the COLOR II trial established that it gave similar oncological outcomes compared to an open approach[ 8 , 9 ] and further studies showed it resulted in shorter length of stay, less pain and quicker resumption of normal diet[ 10 , 11 ]. The main reason behind these proven advantages of the laparoscopic TME is the reduced surgical trauma and tissue handling compared to open TME.…”
Section: Discussionmentioning
confidence: 99%
“…Total mesorectal excision (TME) performed either by open or laparoscopic technique is an accepted gold standard treatment of rectal cancer worldwide. Laparoscopic TME (LTME) has apparent advantages and considered a preferred mode of surgery due to less tissue trauma[ 5 - 11 ]. Due to precision in dissection, stable base unit and better visualization in difficult areas like lower pelvis, the robotic TME (RTME) is also considered a possible alternative to LTME[ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…With advancements in surgical technology, particularly in the fields of laparoscopy and robotics, and trends towards decreasing invasiveness, a robotic mini-mally invasive approach to this highly morbid surgery could be advantageous. Rectal cancer afflicts more than 50 persons per 100,000 and accounts for more than 80,000 deaths per year in Europe [2,3]. Multiple clinical studies have examined outcomes following laparoscopic vs open resection of rectal cancer, the majority demonstrating similar oncological outcomes and improved perioperative outcomes [2][3][4][5][6] ies have examined outcomes following robotic approach to rectal cancer excision.…”
Section: Introductionmentioning
confidence: 99%
“…Rectal cancer afflicts more than 50 persons per 100,000 and accounts for more than 80,000 deaths per year in Europe [2,3]. Multiple clinical studies have examined outcomes following laparoscopic vs open resection of rectal cancer, the majority demonstrating similar oncological outcomes and improved perioperative outcomes [2][3][4][5][6] ies have examined outcomes following robotic approach to rectal cancer excision. Prostate cancer is the most common form of cancer in males and the second leading cause of cancer related death.…”
Section: Introductionmentioning
confidence: 99%